2019
DOI: 10.3389/fmars.2019.00336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Performance of Photographs for Marine Citizen Science Applications

Abstract: Long-term measurements are imperative to detect, understand, and predict changes in coastal biological communities, but can be both costly and difficult to implement. Here, we compare measurement methods used to document community structure and assess changes in marine systems, and explore potential applications in citizen science. The use of photographs for species identifications and monitoring has become a popular and useful data collection tool, but its use requires evaluation of its effectiveness in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Because it can be difficult to identify species even with detailed morphological analyses (Newcomer et al 2019), we maximized the precision of this photo analysis by training the photo observer on life communities sampled and analyzed in the laboratory. We conducted a quality assessment of our photo analysis by comparing data from the panels sampled in 2019, that were analyzed with imageanalysis and taxonomic analysis in the laboratory.…”
Section: Photographic Processingmentioning
confidence: 99%
“…Because it can be difficult to identify species even with detailed morphological analyses (Newcomer et al 2019), we maximized the precision of this photo analysis by training the photo observer on life communities sampled and analyzed in the laboratory. We conducted a quality assessment of our photo analysis by comparing data from the panels sampled in 2019, that were analyzed with imageanalysis and taxonomic analysis in the laboratory.…”
Section: Photographic Processingmentioning
confidence: 99%
“…The monitoring was carried out for three consecutive years (2018-2020) by applying a standardized protocol developed by the Smithsonian Environmental Research Center (Edgewater, MD, United States) that is being used to detect and track NIS in the U.S as well as Canada, Ecuador, and Panama (see also de Rivera et al, 2005;Gartner et al, 2016;Simkanin et al, 2016;Marraffini et al, 2017;Tracy et al, 2017;Chang et al, 2018;Jurgens et al, 2018;Newcomer et al, 2018Newcomer et al, , 2019Carlton, 2019;Torchin et al, 2021). A total of 50 PVC settlement panels (14 × 14 cm) were deployed in the summer of each year in the Gulf of La Spezia, allocating 10 panels in each site.…”
Section: Monitoring Protocolmentioning
confidence: 99%
“…Moreover, species watch cards and a reporting system for target species could be set up for naturalist guides and visitors. Newcomer et al (2019) have shown that photographs taken by tourists have the potential to be used for marine invertebrate identifications, although they do not capture as many species as identifications of fouling communities in the laboratory. In Galapagos, the DiveStat program (Moity et al., 2019) has started collecting information about species sightings from tourists and park rangers, and could be complemented as to include characteristic NIS.…”
Section: Discussionmentioning
confidence: 99%